An approach to extract RESTful services from web applications. (2015) - Upadhyaya, Bipin; Zou, Ying; Khomh, Foutse
The web is the largest database with a huge amount of information and services primarily intended for human users. A user performs different tasks on the web, such as reserving a table in a restaurant. The reuse of web application components would offer greater productivity and ease the maintenance of web applications. The focus of this paper is to circumvent this limitation by proposing an approach to interactively identify reusable web tasks in a web application. We perform a case study on 21 real world web applications from four domains. We identify tasks and services from these web applications. Results show that our proposed approach can identify tasks correctly with a precision of 89% and a recall of more than 90%. Our proposed approach identifies relations among tasks with a precision of 86% and 100% recall. Our approach semi-automatically extracts reusable tasks and represent each task as a RESTful service.